2022
DOI: 10.1002/solr.202101071
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Stability of Indium Tin Oxide and Functional Layers for Semitransparent Back‐Contact Applications on Cu(in,Ga)Se2Solar Cells

Abstract: Herein, a detailed study of the stability of different ITO‐based back‐contact configurations (including bare ITO contacts and contacts functionalized with nanometric Mo, MoSe2, and MoS2 layers) under the coevaporation processes developed for the synthesis of high‐efficiency Cu(In,Ga)Se2 (CIGSe) solar cells is reported. The results show that bare ITO layers can be used as efficient back contacts for coevaporation process temperatures of 480 ºC. However, higher temperatures produce an amorphous In–Se phase at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 57 publications
3
8
0
Order By: Relevance
“…The likeliest hypothesis is that temperatures of 600°C and above significantly degrade the FTO back contact/interface. A similar effect has been previously observed in the case of other TCO back contacts (ITO), which showed a detrimental influence on the solar cells' efficiency when the deposition temperatures increased above 600°C due to the appearance of the In–Se amorphous phase at the absorber/back contact interface 12 …”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…The likeliest hypothesis is that temperatures of 600°C and above significantly degrade the FTO back contact/interface. A similar effect has been previously observed in the case of other TCO back contacts (ITO), which showed a detrimental influence on the solar cells' efficiency when the deposition temperatures increased above 600°C due to the appearance of the In–Se amorphous phase at the absorber/back contact interface 12 …”
Section: Resultssupporting
confidence: 78%
“…It was found that the insertion of an ultrathin Mo layer at the absorber/TCO interface markedly improved the solar cells' performance, which can be ascribed to the formation of a MoSe 2 interlayer acting as hole‐selective material. Our group recently observed a similar trend working on lower band gap CIGS devices, 12 as well as with a wider bandgap (1.4 eV) CIGSe material with a 68% Ga content, 13 which seems to indicate that observations made on the low Ga content are to some extent transferrable to the higher Ga counterpart despite the modified band profile.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Furthermore, the Raman spectra and X‐ray diffraction (XRD) are applied to check the component and phase of MoSe 2 on the Mo foil. The Raman peaks 165 and 285 cm −1 corresponding to two weak vibration modes of E 1g and E 2g , and 242 cm −1 corresponding to the strong vibration mode of A 1g , [ 40 ] are typical peaks of MoSe 2 (Figure S2d, Supporting Information). As shown in the XRD spectra (see Figure 4e), the peaks of 26.1° and 58.7° match well with the standard PDF cards of MoSe 2 (pdf#20‐0757) and Mo (pdf#42‐1120) phases, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Fonoll-Rubio et al suggested the formation of an In-Se compound when CIGS is grown on ITO at T abs > 480 °C, deteriorating the electrical and optical properties of the TBC. [41] Since others measured decent solar cell characteristics using bare ITO back contacts for T abs up to 600 °C, [16] the evolution of secondary phases obviously depends on the absorber deposition process as well. For further details, Table S1 in Supporting Information lists the important contact properties of all identified works on CIGS-based solar cells with TBCs (not claiming completeness).…”
Section: Introductionmentioning
confidence: 99%